2019
DOI: 10.1109/access.2019.2961450
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative User-Level Customized Modeling and Simulation Environment for Smart Manufacturing

Abstract: As smart factories are emerging, the importance of modeling and simulation (M&S) continues to increase in the production system. As a result, various commercial tools and environments are provided for production simulation, and manufacturing companies are also applying them to establish a smart manufacturing system. This is used in various ways, such as optimal layout design, scheduling, and fault diagnosis using the acquired smart manufacturing model. However, these model constructions are generally done thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…The findings presented in the literature review revealed that the main features of the application of Industry 4.0 technologies in manufacturing setting are real-time overview, decentralization, ability to connect devices via IoT and gather real-time data, cloud computing for computationally costly models and transparency and trackability of individual products (Figure 6A). As smart manufacturing solutions tend to be costly investments, a lower level of expense is a preferrable feature of various solutions [51,70,92,112]. [48,87,91,95,108].…”
Section: Discussionmentioning
confidence: 99%
“…The findings presented in the literature review revealed that the main features of the application of Industry 4.0 technologies in manufacturing setting are real-time overview, decentralization, ability to connect devices via IoT and gather real-time data, cloud computing for computationally costly models and transparency and trackability of individual products (Figure 6A). As smart manufacturing solutions tend to be costly investments, a lower level of expense is a preferrable feature of various solutions [51,70,92,112]. [48,87,91,95,108].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of Industry 4.0, production in the factories will be more flexible and must be more intelligent. Related research topics about automated production control systems [18]; automation of product, design, management, and control systems [2]; intelligent manufacturing [20,21]; and CPS [3,6] have been proposed. Whether the research topic is intelligent manufacturing, CPS, or automated production control systems, most people tend to study methods and introductions and do less with the combination and application of the actual production line.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, scholars are discussing a pluggable software Orchestrator [18], which can automatically extract instructions from a given input, set the factory process accordingly, and execute production by itself to realize a dynamic resource arrangement. The automation of a robot control system based on an automatic programming environment minimizes user rework and analysis time when there is a frequent need to redistribute the robot task through robot self-observational learning, independent reprogramming, or-through the integration of the M&S environment-maintain and promote model reuse, and to provide an automatic model-generation function to obtain the best solutions [19,20]. At present, even internal personnel training of enterprises has introduced intelligent learning [21].…”
Section: Introductionmentioning
confidence: 99%
“…Authors in ref. [33] have designed a solution approach for user-level customized modelling and simulation in production facilities, which can be used as starting point for the implementation of the ULC Module. However, further research is necessary at the network level to determine the number of modelling levels that should exist and which actor utilizes each level.…”
Section: Platform Architecturementioning
confidence: 99%